Eyeglasses on the cheap [tabletop lens molding]. - Jones, W.D (IEEE spectrum)
A graduate student inventor in MIT, Saul Griffith, sets his sights on correcting the world's vision problems with tabletop lens molding. He developed a system that can provide a vision-impaired person with low-cost lenses in a matter of minutes. This articles presents the advantages of this system and how the machine makes glasses and diagnose eye problems for a lesser price.